Incidence and Risk Factors for Antiplatelet Therapy–Related Bleeding Complications Among Elderly Patients After Coronary Stenting: A Multicenter Retrospective Observation - Qian, Yanxia; Xu, Bing; Qian, Xiaodong; Cao, Lu; Cheng, Yujia; Liu, Xinjian; Bai, Song; Han, Zhijun; Wang, Junhong (Frontiers in Pharmacology, 2021)
Purpose: To study risk factors of bleeding events and assess the performance of PRECISE-DAPT score in elderly patients ≥75 years with one-year dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI). Methods: A total of 940 patients ≥75 years receiving one-year DAPT following PCI were retrospectively enrolled into the study. Multivariable logistic regression analysis were conducted to identify risk factors of antiplatelet-related bleeding complications. Receiver operating characteristic (ROC) curve analysis and the Delong test was performed to obtain the optimized PRECISE-DAPT score. Results: A total of 89 (9.47%) patients suffered from bleeding complications and 37 (3.94%) had Bleeding Academic Research Consortium (BARC) ≥2 type bleeding events. We stratified PRECISE-DAPT score in tertiles (T1:≤23; T2:24 to 32; T3:≥33) and found BARC ≥2 type bleeding occurred more frequently in T3 than T1 and T2 (8.25% vs. 1.46% vs. 2.40%, p<0.05). ROC curve analysis revealed that the cut-off PRECISE-DAPT score for BARC ≥2 type bleeding prediction was 33. As compared to the ROC of the current recommended cut-off score of 25 (AUC: 0.608), the Delong test indicated significantly improved ability for predicting BARC ≥2 type bleeding events using the proposed cut-off value of 33 with the AUC of 0.676 (p=0.03) and the Brier Score was 0.04. Multivariable logistic regression analysis demonstrated PRECISE-DAPT score ≥33 (OR:3.772; 95%CI(1.229, 11.578); p=0.02) was associated with BARC ≥2 type bleeding, together with history of hemorrhagic stroke (OR:6.806; 95%CI(1.465, 31.613); p=0.014), peptic ulcer (OR:3.871; 95%CI(1.378, 10.871); p=0.01) or myocardial infarction (OR:3.081; 95%CI(1.140, 8.326); p=0.027). Conclusions: Higher PRECISE-DAPT score of 33 might be a more reasonable cut-off value for predicting BARC ≥2 type bleeding risk in CAD patients ≥75 years. In addition, history of hemorrhagic stroke, peptic ulcer and myocardial infarction were risk factors of BARC ≥2 type bleeding events.